PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN PENDEKATAN INKUIRI DENGAN PEMBELAJARAN KONVENSIONAL PADA MATA PELAJARAN EKONOMI KELAS XI IPS SMA N 14 PADANG - Afrischa, Wan Lady; Tanjung, Mirna; Susanti, Dessi (Pendidikan Ekonomi, 2013)
AbstractThe research was motivated by the low learning outcomes studied economics . This is caused by several factors , among the contributing factors is the method or approach used by teachers is still conventional , less students are actively involved in the learning and assessment that is used is still assessing the results of the assessment process yet . The purpose of this study was to look at differences in student learning outcomes using the inquiry approach to learning directly in SMA Negeri 14 Padang .This research is experimental research and research design used was purposive sampling . The population in this study were all students of class XI IPS SMA Negeri 14 Padang were registered in 2013/2014 , while the samples in this study were students of class XI IPS as an experimental class 5 and class XI IPS 3 as the control class .The data analysis technique used is the t test for normal distribution of data and groups of data have a homogeneous variance . The results showed that the average learning outcomes experimental class is 89.8 while the average of the control class learning outcomes is 80.83 . Based on the analysis of the data obtained , t = 3.631 > table = 1,654 then the decision is H0 is rejected and H1 is accepted .So it can be concluded that there are differences in student learning outcomes using the inquiry approach with conventional learning , where learning using an inquiry approach to higher learning outcomes than learning outcomes using conventional learning . This study is expected to be beneficial to all parties including the school principal to socialize inquiry approach to economic studies teachers in particular , for teachers to be able to apply the approach to inquiry and research institute, and later as reference material for future research .Â Keywords : Inquiry Approaches and Learning Outcomes